Memory, Attention and Emotions in an Educational Context: A Neuroscientific Perspective - Mocanu, Lăcrămioara (Didactica Danubiensis, 2026)
Understanding the brain mechanisms underlying learning is becoming increasingly relevant for optimizing the educational process. This article explores the complex relationship between memory, attention, and emotions in the educational context, drawing on recent discoveries in neuroscience. The analysis focuses on how these three components interact at the brain level and influence students’ academic performance. We will examine the neuroanatomical structures involved in memory processes, the mechanisms by which selective attention facilitates information retention, and the fundamental role of emotions in consolidating learning. The article also provides insight into the practical implications for teachers, suggesting that integrating neuroscientific principles into pedagogical practice can transform traditional teaching methods. The conclusions highlight the need for a holistic approach in education, which takes into account the complexity of brain functioning and the interdependence between cognitive and affective processes.